An evaluation of the value of relationship in a workplace - Pyiki, Hauwa Bawa; Nnaji, Florence Oluchi; Sambo, Maryam; Mohammed, Ali (Journal of Professional Secretaries and Office Administrators, 2014)
This Paper titled An Evaluation of Relationship in a Work Place believed that relationship in a work place is a powerful Instrument that will enhance harmony amongst staff, increase productivity and profit margin of every organization. The paper examined the concept of work relationship, values and Ethics that can keep relationship going, the necessity for interpersonal skills, human relation as well as the value of relationship in a work place. The paper concluded that collaboration and team work amongst workers would act as a catalyst for increasing productivity. It recommends amongst others that managers should esteem relationship very high in every organization because relationship is rooted in values.